The silent struggle of Japan’s ‘young carers’ - Takao, Yasuo (Crawford School of Public Policy, Australian National University, 2025)
The rise of ‘young carers’ — children under 18 who take on adult caregiving roles — in Japan reflects the lingering influence of a patriarchal family system and growing care demands amid an aging population. Insufficient support systems and a lack of self- and public awareness about the issue make it difficult to identify and assist these children. Without stronger measures, young carers face risks to their education, wellbeing and rights, underscoring the urgent need for recognition and comprehensive support.